Financial instruments characterization for water governance in Colombia (2020)
Conceps of water resource governance and water resource gobernability are significantly different. The first one concerns to public, private and social actors. Those interact in order to build a system of institutional arrangements in water resource management, and stablish strategies and citizen actions. The second one is about the govern performance of the sociopolitical system. Is also undestood as an imposition of public policies in water resource management, with a lack of knowledge of the interests and expectations of the communities settled in these territories. Colombia is currently focused on managing the supply of the resource with a growing need for investment that exceeds national capacities. The need to explore new alternatives for financing becomes evident, with the intention of increase the service efficiency and assure the water supply and environmental services. Good water governance generates elements that contribute to the economy, due to its capacity to generate financial resources, either indirectly (public budget), or through payments specifically allocated to the entity that manages the resources. This document will evaluate the contributions of the financial instruments currently used, analyzing payment for public services, transfers, water funds and some public-private partnerships that have been developed in some of the most important basins in the national territory.